EMPIRICAL ANALYSIS OF MONEY DEMAND AND SHOCKS IN WAEMU - KOUADIO Kouamé Jean-Jacques; N’GORAN Christian , Florent Kohounsa; OUATTARA Soman Désiré-Ferdinand; TANO , Ghislain Gerard (Revue Internationale du Chercheur, 2022)
The study of the demand for money is not only to grasp the quantity of money on hand. This is to ask the fundamental concern, is the economic definition of the demand for money intuitive? The answer to this question helps monetary policymakers formulate more effective policy. Using cointegration regression and the error correction model method over the period 1960 to 2009, applied to the Ivorian economy. Our results suggest that M1 is not cointegrated with its determinants real income and expected inflation and therefore unstable. As for the broader definition of M2 money, a long-term equilibrium relationship with its determinants is found over the period 1960-2009. M2 money demand is co-integrated with real output and expected inflation at the 5% significance level. The income elasticity for M2 is 0:716 suggesting that M2 plays more of a transactional role than its other unit of account or store of value functions. Short-term dynamics of M2 money demand outcomes using error-correction modeling indicate that a deviation from the long-term equilibrium path could be restored in about 24 days. The money demand shocks that occurred after 1980 were stronger and therefore underwent prolonged periods of adjustment. Finally, we conclude that M2 remains the most appropriate definition of money for the Ivorian economy, implying that it can be used as an alternative to the interest rate for a long-term monetary policy instrument.